EFFECTS OF WOMEN ENTREPRENEURIAL DEVELOPMENT ON DOMESTIC VIOLENCE REDUCTION IN NIGERIA - Agu, M. N.; Mohammed, H. I.; Paul, V. (Journal of Agripreneurship and Sustainable Development, 2020)
The study was conducted to examine the effects of women entrepreneurial development on domestic violence reduction in Nigeria. A mixed method approach was used and the population of the study constituted selected women entrepreneurs across Nigeria. The study sampled 839 respondents using Top-man formula for sample size determination. The instrument for the study was questionnaire that used likert scale format. The study adopted content validity for the instruments and Cronbach alpha method of internal consistency to determine the reliability of the questionnaire. Data analysis was carried out using multiple regressions with the aid of content thematic analysis of SPSSv21. The study concluded that women who engaged in entrepreneurial activities support their homes; and they were considered as assets not liabilities by their husbands and therefore, earn respect. Domestic violence against women constitutes a major setback to agricultural activities in the Study Area. The study, therefore, recommended that women should be given every encouragement both financially and emotionally to embark on entrepreneurial activities such as opportunities to occupy reasonable positions in government both politically and career appointments to display their talents; and the farmers especially from the women extraction be given full protection against herdsmen at both on farms and at home. There is also need for non-governmental organizations (NGOs) who are also key components in any sustainable human development agenda to end or reduce violence against women by rendering community services through the creation of adequate awareness to the general public.